2021
DOI: 10.1177/1753193421991318
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the incidence of pin site infection in hand surgery with the use of a protocol from Ilizarov

Abstract: Reported pin site infection rates in Kirschner wire fixation in the hand and wrist vary from 2% to 35%. In our unit we follow a strict pin site management protocol adapted from the Russian Ilizarov Scientific Centre. This study aims to identify if our current protocol reduces the incidence of pin site infection in hand and wrist surgery, and improves wire survival rates, to a level where exposed wires can be used safely. A retrospective review of 200 patients, treated with 369 percutaneous wires, in our hand s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In a systematic review, Karantana et al [ 33 ] found the incidence of pin site infection was 8% (range, 0% to 15%), which can be treated by pin site care and rarely requires antibiotics or early wire removal. Solari et al [ 34 ] retrospectively reviewed 200 patients treated with 369 percutaneous K-wires. Pin site infection was diagnosed in 9 patients (5%), and the wire survival rate was 99.5%.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review, Karantana et al [ 33 ] found the incidence of pin site infection was 8% (range, 0% to 15%), which can be treated by pin site care and rarely requires antibiotics or early wire removal. Solari et al [ 34 ] retrospectively reviewed 200 patients treated with 369 percutaneous K-wires. Pin site infection was diagnosed in 9 patients (5%), and the wire survival rate was 99.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Kirschner wire fixation is often used for hand and wrist fractures. There is a good deal of evidence that superficial wires are associated with a high rate of infection and that burying the wires beneath the skin decreases the frequency of this complication [70][71][72] .…”
Section: Fracture Carementioning
confidence: 99%
“…Reported pin site infection rates vary from 2% to 35%. [2] Though antiseptics are used by many surgeons to prevent pin site infections, clear-cut evidence to support their use remains uncertain. Also the recommendation for the frequency of pin site care varies from four times a day to as much as once in a week.…”
Section: Introductionmentioning
confidence: 99%